DYNAMIC CAPABILITIES - ARE THEY PROFITABLE? - Niels Nolsoe Grunbaum; Marianne Stenger (European Scientific Journal, ESJ, 2013)
The consequences of dynamic capabilities (i.e. innovation performance and profitability) is an under researched area in the growing body of literature on dynamic capabilities. This study aims to examine the relationship between dynamic capabilities, innovation performance and profitability of small and medium sized enterprises operating in volatile environments. A multi-case study design was adopted as research strategy. The findings reveal a positive relationship between dynamic capabilities and innovation performance in the case enterprises, as we would expect. It was, however, not possible to establish a positive relationship between innovation performance and profitability. Nor was there any positive relationship between dynamic capabilities and profitability. The main contribution of this study is a better understanding of the realm of small and medium sized enterprises’ internal and external business atmosphere. A sphere dominated, on the positive side, by high product quality, high product innovation, high flexibility, a very low return rate of failed products, a flat organization structure and an involving style of leadership. On the opposite pole it was dominated by a lack of systematism, assessment, monitoring, marketing speculations and feasibility calculation. Furthermore, the sphere was dictated by asymmetric supplier-customer relationships and negotiation power leading, among other possible factors, to meager profitability.